Loofah sponge-shaped flexible porous carbon nanotube film as well as preparation method and application thereof
Through electrospinning method and solvent heat induction technology, a loofah-shaped flexible porous carbon nanotube membrane was prepared, which solved the environmental and efficiency problems of the existing porous carbon material preparation methods, and achieved the effect of efficient adsorption and CO2 capture.
Patent Information
- Application Number
- CN202411744652.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-01
- Publication Date
- 2025-04-04
AI Technical Summary
The existing methods for preparing porous carbon materials often require long time or harsh conditions, and the reagents used may be harmful to the environment, and there is a lack of simple and environmentally friendly preparation methods.
PAN/PVP nanofiber membrane was prepared by electrospinning method, and a loofah-like flexible porous carbon nanotube membrane was prepared by ethylene glycol solvent heat induction and calcination carbonization process.
A loofah-shaped flexible porous carbon nanotube membrane with high specific surface area, good adsorption performance and environmental protection characteristics was achieved, which is suitable for adsorption of organic pollutants and CO2 capture.
Smart Images

Figure CN119753944A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of porous carbon nanotube film preparation, and in particular to a loofah-shaped flexible porous carbon nanotube film and a preparation method and application thereof. Background Art
[0002] Porous carbon materials have attracted wide attention in many application fields such as catalysis, energy storage, electrochemistry, and adsorption due to their high specific surface area, excellent electrical conductivity, and physical and chemical stability. Among them, hierarchical porous carbon materials have attracted much attention due to their advantages such as low density, light weight, multiple active sites, strong gas-liquid permeability, adjustable pore structure, and good adsorption performance. The preparation methods of hierarchical porous carbon materials include acid-base etching, organic foam impregnation, etc. However, most of these methods require a long time or harsh conditions, and the use of reagents may be harmful to the environment. Therefore, it is necessary to study a simple and environmentally friendly porous carbon material to solve the above problems.
[0003] Electrospinning technology has become one of the main ways to effectively prepare nanofiber membranes with its advantages of simple manufacturing equipment, low cost, a wide variety of spinnable materials, and controllable process, and can well solve the problem of difficult recovery of nanofiber membranes. Polyacrylonitrile (PAN) is widely used as a precursor of nanocarbon fibers because of its low cost, good spinning performance, and high carbonization rate. It has a very broad application prospect in the preparation of functional materials such as electromagnetic wave absorption, catalysis, and antibacterial. Therefore, this application uses PAN to prepare a loofah-like flexible porous carbon (LPC) nanotube membrane by electrospinning and combining ethylene glycol solvent thermal induction strategy and carbonization process, which is applied in the adsorption of organic pollutants. Summary of the invention
[0004] Based on the above, the purpose of the present invention is to provide a loofah-like flexible porous carbon nanotube membrane and a preparation method and application thereof, so as to prepare a simple and environmentally friendly porous carbon material for use in the adsorption of organic pollutants.
[0005] To achieve the above object, the present invention adopts the following technical solutions:
[0006] A method for preparing a loofah-shaped flexible porous carbon nanotube film comprises the following steps:
[0007] Dissolving polyacrylonitrile (PAN) and polyvinyl pyrrolidone (PVP) in N,N-dimethylformamide (DMF) and stirring to obtain a uniform precursor spinning solution; electrospinning the precursor spinning solution and drying to obtain a PAN / PVP nanofiber membrane;
[0008] The PAN / PVP nanofiber membrane is cut into preset sizes, placed in a high-pressure reactor, ethylene glycol is added, a solvent thermal induction reaction is carried out, and then it is repeatedly washed with deionized water to obtain a bionic loofah-like porous PAN nanotube membrane, and then a calcination carbonization reaction is carried out to obtain a loofah-like flexible porous carbon nanotube membrane.
[0009] As a preferred solution of the method for preparing a loofah-like flexible porous carbon nanotube membrane, the mass ratio of the PAN to the PVP is 1:1, and the concentration of the PAN in the DMF is 1 g / mL.
[0010] As a preferred embodiment of the method for preparing a loofah-like flexible porous carbon nanotube film, the concentration of PAN relative to the ethylene glycol is 0.3 g / mL.
[0011] As a preferred solution for the preparation method of a loofah-like flexible porous carbon nanotube membrane, during the electrospinning process, a collecting device is used to collect the electrospinning product, the spinning temperature is 20-30°C, the relative humidity is 40-50%, and a 11-13 kV DC high voltage is connected.
[0012] As a preferred solution of the method for preparing a loofah-like flexible porous carbon nanotube film, in the drying process after electrospinning, the drying temperature is 50 to 70° C. and the drying time is 1 to 3 hours.
[0013] As a preferred solution of the method for preparing a loofah-like flexible porous carbon nanotube film, during the solvent thermal induction reaction, the reaction temperature is 170 to 190° C. and the reaction time is 2 to 4 hours.
[0014] As a preferred scheme for the preparation method of a loofah-shaped flexible porous carbon nanotube membrane, during the calcination carbonization reaction, the temperature is slowly increased to 260-280°C at a rate of 1-2°C / min in an air atmosphere and kept warm for 1-3 hours, and then the temperature is increased to 700-900°C at a heating rate of 2-4°C / min in an argon atmosphere and kept warm for 1-3 hours.
[0015] A loofah-shaped flexible porous carbon nanotube film is prepared by any of the above-mentioned preparation methods.
[0016] The invention discloses an application of a loofah-shaped flexible porous carbon nanotube membrane, which is applied in the adsorption of organic pollutants based on the loofah-shaped flexible porous carbon nanotube membrane.
[0017] The beneficial effects of the present invention are:
[0018] The present invention provides a luffa-like flexible porous carbon nanotube membrane and its preparation method and application. A two-component PAN / PVP nanofiber membrane is prepared by an electrospinning method. Based on the phase separation phenomenon between PAN / PVP, the PVP component is selectively removed by combining ethylene glycol (EG) solvent thermal induction, and then a PAN-based flexible porous carbon nanotube (LPC) with a luffa-like structure is prepared by a calcination process. When the EG solvent thermal treatment time is 2h and the calcination temperature is 900℃, the prepared LPC-2-900 has the largest specific surface area of 878.909m 2 ·g -1 At the same time, the maximum adsorption capacity of methylene blue dye (MB) at room temperature is 528.6 mg·g -1 The cycle performance is good, and the maximum CO2 capture performance at 273K, 101kPa is 2.83mmol·g -1 , which has practical value in removing MB and efficiently capturing CO2. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments of the present invention. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the contents of the embodiments of the present invention and these drawings without paying any creative work.
[0020] Figure 1 are the SEM images of the reaction products induced by solvothermal reaction in different solvents (the insets show the corresponding digital photos), (A1, A2) PAN / PVP, (B1, B2) PAN / PVP-EG-2, (C1, C2) PAN / PVP-E-2, (D1, D2) PAN / PVP-W-2;
[0021] Figure 2 are the SEM images of the reaction products after EG solvothermal induction at different times, (A1, A2) PAN / PVP-EG-2, (B1, B2) PAN / PVP-EG-3, (C1, C2) PAN / PVP-EG-4;
[0022] Figure 3 The SEM images of the reaction products calcined and carbonized at different temperatures, (A) LPC-2-700, (B) LPC-2-800, (C, D) LPC-2-900, TEM and HRTEM images, (E, F) LPC-2-900;
[0023] Figure 4FT-IR spectra: (a) PAN / PVP; (b) PAN / PVP-EG-2; (c) PAN / PVP-E-2; (d) PAN / PVP-W-2;
[0024] Figure 5 are (A) XRD patterns and (B) Raman spectra of different products, (a) LPC-2-700, (b) LPC-2-800, (c) LPC-2-900, (d) C-900;
[0025] Figure 6 (A) N2 adsorption-desorption isotherms and (B) pore size distribution curves of different nanotube membranes, (a) PAN / PVP, (b) PAN / PVP-EG-2, (c) PAN / PVP-EG-3, (d) PAN / PVP-EG-4; (C) N2 adsorption-desorption isotherms and (D) pore size distribution curves of different carbon nanofiber membranes, (a) LPC-2-700, (b) LPC-2-800, (c) LPC-2-900, (d) LPC-3-900, (e) LPC-4-900, (f) C-900;
[0026] Figure 7 (A) Maximum adsorption capacity of LPC-2-900 at different MB concentrations; (B) Curve of adsorption capacity versus time (C0 = 300 mg / L; adsorbent mass = 5 mg; T = 303.15 K); (C) Pseudo-first-order kinetic fitting; (D) Pseudo-second-order kinetic fitting; (E) Isoelectric point test of LPC-2-900; (F) Cyclic adsorption performance of LPC-2-900;
[0027] Figure 8 are (A) CO2 adsorption curves at 273K and (B) bar graphs of the maximum CO2 adsorption capacity at 273K, 101kPa, (a) LPC-2-700, (b) LPC-2-800, (c) LPC-2-900, (d) C-900;
[0028] Fig. 9 Optical images of different polymer solution precursors under microscope and SEM images of nanofiber membranes (the inset shows the corresponding digital photos), (a) PVP, (b) PAN, (c) PAN / PVP, (d) PAN, (e) PAN-EG, (f) PAN / PVP, (g) PAN / PVP-EG. DETAILED DESCRIPTION
[0029] For ease of understanding of the present invention, the present invention will be described more fully below. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive. Unless otherwise defined, all technical and scientific terms used in the present invention belong to the technical field of the present invention.
[0030] The present invention provides a method for preparing a luffa-shaped flexible porous carbon nanotube film, comprising the following steps:
[0031] S100, dissolving polyacrylonitrile (PAN) and polyvinyl pyrrolidone (PVP) in N,N-dimethylformamide (DMF) and stirring to obtain a uniform precursor spinning solution; electrospinning the precursor spinning solution, drying it, and obtaining a PAN / PVP nanofiber membrane;
[0032] Specifically, the mass ratio of PAN to PVP is 1:1, and the concentration of PAN in the DMF is 1 g / mL; during the electrospinning process, a collecting device is used to collect the electrospinning product, the collecting device is placed 15 to 20 cm away from the needle tip of the syringe, the spinning temperature is 20 to 30°C, the relative humidity is 40 to 50%, and 11 to 13 kV DC high voltage is connected. Among them, the Mw of polyvinyl pyrrolidone is preferably 1,300,000, and the Mw of polyacrylonitrile is preferably 150,000.
[0033] Specifically, during the drying process after electrospinning, the drying temperature is 50-70° C. and the drying time is 1-3 hours.
[0034] S200, cutting the PAN / PVP nanofiber membrane according to a preset size, placing it in a high-pressure reactor, adding ethylene glycol, performing a solvent thermal induction reaction, and then repeatedly washing it with deionized water to obtain a bionic loofah-like porous PAN nanotube membrane, and then performing a calcination carbonization reaction to obtain a loofah-like flexible porous carbon nanotube membrane.
[0035] Specifically, the concentration of PAN relative to ethylene glycol was 0.3 g / mL.
[0036] Specifically, during the solvent thermal induction reaction, the reaction temperature is 170-190°C and the reaction time is 2-4h; during the calcination carbonization treatment, the temperature is slowly increased to 260-280°C at a rate of 1-2°C / min in an air atmosphere and kept warm for 1-3h, and then the temperature is increased to 700-900°C at a heating rate of 2-4°C / min in an argon atmosphere and kept warm for 1-3h.
[0037] The present invention will be further described below by means of specific examples.
[0038] Example 1
[0039] 0.6g PAN and 0.6g PVP were dissolved in 6mL DMF and stirred for 6h to obtain a uniform precursor spinning solution; the precursor spinning solution was transferred to a steel needle syringe connected to a 12kV DC high voltage, and the collection device was electrospun at a distance of 15cm from the tip of the steel needle. The electrospinning conditions were: temperature 25℃, relative humidity 45%. The spun nanofiber membrane was placed in an oven at 60℃ for 2h to remove the residual solvent to obtain a PAN / PVP nanofiber membrane;
[0040] The PAN / PVP nanofiber membrane was cut into small square pieces with a side length of 3 cm according to the preset size, placed in a stainless steel high-pressure reactor lined with Teflon, and 20 mL of ethylene glycol was added for high-temperature reaction. The mixture was sealed and reacted at 180 °C for 2 h, and then washed repeatedly with deionized water to obtain a biomimetic loofah-like flexible porous PAN nanotube membrane (named PAN / PVP-EG-2).
[0041] The bionic loofah-like flexible PAN nanofiber membrane was slowly heated to 270°C at a heating rate of 1°C / min in an air atmosphere and kept warm for 1 h, and then the temperature was increased to 900°C at a heating rate of 3°C / min in an argon atmosphere and kept warm for 1 h to obtain a loofah-like flexible porous carbon nanotube membrane (LPC), named LPC-2-900.
[0042] Example 2
[0043] The preparation process and reaction conditions are basically the same as those in Example 1. Ethylene glycol is used as the solvent and the reaction is carried out in a high-pressure reactor for 3 hours to prepare a bionic loofah-like flexible porous PAN nanofiber membrane. After a carbonization reaction at 900°C, a loofah-like flexible porous carbon nanotube membrane (LPC) is prepared, named LPC-3-900.
[0044] Example 3
[0045] The preparation process and reaction conditions are basically the same as those in Example 1. Ethylene glycol is used as the solvent and the reaction is carried out in a high-pressure reactor for 4 hours to prepare a bionic loofah-like flexible porous PAN nanofiber membrane. After a carbonization reaction at 900°C, a loofah-like flexible porous carbon nanotube membrane (LPC) is prepared, named LPC-4-900.
[0046] Example 4
[0047] The preparation process and reaction conditions are basically the same as those in Example 1. Ethylene glycol is used as the solvent and the reaction is carried out in a high-pressure reactor for 2 hours to prepare a bionic loofah-like flexible porous PAN nanofiber membrane. After a carbonization reaction at 800°C, a loofah-like flexible porous carbon nanotube membrane (LPC) is prepared, named LPC-2-800.
[0048] Example 5
[0049] The preparation process and reaction conditions are basically the same as those in Example 1. Ethylene glycol is used as the solvent and the reaction is carried out in a high-pressure reactor for 2 hours to prepare a bionic loofah-like flexible porous PAN nanotube membrane. After a carbonization reaction at 900°C, a loofah-like flexible porous carbon nanotube membrane (LPC) is prepared, named LPC-2-700.
[0050] In order to further illustrate the key points of this patent, a comparative case is added for illustration.
[0051] Comparative Example 1
[0052] The preparation process and reaction conditions were basically the same as those in Example 1, but PVP was not added for the reaction. Cross-linked nanofibers were prepared as a single-component PAN nanofiber membrane, named PAN-EG.
[0053] Comparative Example 2
[0054] The preparation process and reaction conditions were basically the same as those in Example 1, but no solvent was added and the solvothermal reaction was not carried out in a high-pressure reactor. Smooth nanofibers were obtained, named PAN / PVP, and carbonized at 900°C. The obtained nanofibers were named C-900.
[0055] Comparative Example 3
[0056] The preparation process and reaction conditions were basically the same as those in Example 1, and water was used as the solvent for the solvothermal reaction to obtain cracked nanofibers, which were named PAN / PVP-W-2.
[0057] Comparative Example 4
[0058] The preparation process and reaction conditions were basically the same as those in Example 1, and ethanol was used as the solvent for the solvothermal reaction to obtain porous nanofibers, which were named PAN / PVP-E-2.
[0059] The preparation formulas of the bionic loofah-like PAN porous carbon nanotube membranes prepared in the above examples and comparative examples are shown in Table 1.
[0060] Table 1 Preparation formula of biomimetic loofah-like flexible PAN porous nanotube membrane
[0061]
[0062] In order to further study the adsorption performance of the loofah-like flexible porous carbon nanotube film prepared in the present application, an adsorption test was conducted on the products prepared in the above embodiments and comparative examples. The adsorption experiment includes:
[0063] Methylene blue (MB) was selected to simulate organic pollutants in water. The effect of the initial concentration of MB on the adsorption capacity of LPC-2-900 was systematically investigated. 5 mg of LPC-2-900 was dispersed in 50 mL of MB solution with concentrations of 50, 100, 200, 300, and 400 mg / L. Then oscillate for 12 hours under dark conditions to reach adsorption-desorption equilibrium. Finally, 2 mL of supernatant was taken (diluted if necessary) and the absorbance at 665 nm was measured using a UV-visible spectrophotometer. At the same time, adsorption kinetics experiments were also carried out, and the kinetic data were analyzed: 5 mg of the sample was dispersed in 50 mL of MB solution with a concentration of 300 mg / L, and 2 mL of supernatant was taken at intervals (diluted if necessary), and the absorbance at 665 nm was measured using a UV-visible spectrophotometer. The maximum adsorption capacity of the MB solution and the adsorption capacity at time t can be calculated according to the following formula:
[0064]
[0065] In the formula, C0 (mg / L), C e (mg / L), C t (mg / L) are the initial concentration, the concentration at adsorption equilibrium and the concentration at time t, m (mg) is the mass of the adsorbent, and V (mL) is the volume of the solution.
[0066] The CO2 adsorption capacity of LPC-2-700, LPC-2-800, LPC-2-900 and C-900 at 273K and 0-101kPa pressure range was tested using a volume meter.
[0067] In addition, in order to further analyze the reaction mechanism, the products prepared in the examples and comparative examples of the present application were also subjected to relevant performance analysis.
[0068] 1. Morphology analysis
[0069] The surface morphology of different examples was characterized by scanning electron microscopy, and digital photos of the examples are shown in the inset. Figure 1 As shown in (A1, A2), the surface of PAN / PVP nanofiber membrane is smooth and the diameter is uniformly about 300nm. Figure 1As can be seen from (BD), after different solvent thermal induction, the morphology of different examples is different, but all of them maintain the original one-dimensional fiber state very well. As can be seen from the illustration, the PAN / PVP nanofiber membrane with a size of 3cm×3cm will shrink after the solvent thermal induction process, and different solvents have different effects on the degree of shrinkage. This is mainly due to the different solubility of the two components PAN and PVP in different solvents. In particular, when the PAN / PVP nanofiber membrane was induced by EG solvent thermally for 2h, it was found that the PAN / PVP-EG-2 nanotube membrane had a unique loofah-like porous morphology, and the average fiber diameter was about 930nm ( Figure 1 B1, B2). When the PAN / PVP nanofiber membrane was treated with ethanol solvent thermal induction for 2 h, Figure 1 As shown in (C1, C2), the PAN / PVP-E-2 nanofiber membrane has a porous morphology with an average fiber diameter of about 470nm. After the PAN / PVP nanofiber membrane was thermally induced by water solvent for 2h, the PAN / PVP-W-2 nanofiber membrane showed a uniform crack-like surface morphology with a fiber diameter of about 960nm ( Figure 1 (D1, D2)), fusion occurs between the fibers. In general, due to the multi-faceted effects of swelling, dissolution, and crystallization of PAN and PVP molecular chains during the solvothermal induction process, the average diameter of the nanofibers increases to varying degrees. In addition, the shrinkage rate of the nanofiber membrane has a direct effect on the diameter of the nanofibers. In summary, the EG solvothermal induction strategy plays a vital role in the formation of luffa-like flexible PAN porous nanotube membranes, while neither the ethanol solvothermal induction strategy nor the water solvothermal induction strategy can obtain a luffa-like porous structure.
[0070] The effect of different EG solvothermal induction times on the morphology of PAN / PVP nanofiber membranes was further investigated by scanning electron microscopy. The PAN / PVP nanofiber membranes were treated with EG solvothermal induction for 2h, 3h, and 4h to obtain the corresponding examples PAN / PVP-EG-2, PAN / PVP-EG-3, and PAN / PVP-EG-4. The results are shown in Figure 2 All PAN / PVP-EG nanotube films have a loofah-like porous morphology, and the average diameter increases from the initial approximately 320 nm to 930, 530, and 610 nm, respectively. In addition, the number and pore size of the nanofibers increase significantly with the extension of the solvothermal reaction time. This may be due to the fact that the swelling, dissolution, crystallization, and other synergistic effects of PAN and PVP molecular chains are enhanced accordingly as the solvothermal induction time is extended.
[0071] The morphology and microstructure of the luffa-like flexible porous carbon nanotube membrane (LPC) were studied by scanning electron microscopy and high energy transmission electron microscopy (HRTEM). The PAN / PVP-EG-2 nanotube membrane was converted into a series of LPCs after carbonization treatment at different temperatures. Figure 3 (AD) It can be seen that after carbonization, all examples still maintain a perfect one-dimensional nanofiber structure. Compared with the average diameter of PAN / PVP-EG-2 of 930nm, the average diameters of LPC-2-700, LPC-2-800 and LPC-2-900 have shrunk. At the same time, it was detected that the number and pore size of the LPCs obtained after carbonization were significantly reduced, which may be the result of fiber shrinkage caused by high temperature. Figure 3 (C, D) shows that LPC-2-900 still maintains a loofah-like porous structure. The unique loofah-like porous structure of LPCs is conducive to increasing the specific surface area and molecular migration channels, thus significantly improving the adsorption performance. Figure 3 The TEM and HRTEM images of LPC-2-900 in (E, F) show that LPC-2-900 has a large number of pores and Figure 3 A large number of micropores were detected in the HRTEM image of (F). Based on the above analysis, both SEM and TEM images show that the LPC-2-900 nanofiber membrane has a loofah-like porous structure, so the EG solvent thermal induction strategy and calcination process are feasible for the biomimetic preparation of loofah-like porous carbon.
[0072] 2. Component and structure analysis
[0073] The functional group composition of the material was analyzed using Fourier transform infrared spectroscopy. Figure 4 In the prepared examples, the wavelengths of the ions were 3400, 3000-2900 and 1454 cm -1 There are absorption peaks near 2245cm and 1450cm, which are attributed to -OH stretching vibration, CH bond stretching vibration and deformation vibration. The remaining main characteristic peaks are attributed to PAN and PVP. -1 The peak at 1680 cm-1 corresponds to the stretching vibration of the C≡N bond and the stretching vibration of C=C in PAN. -1 There is an obvious peak at 1680 cm-1, which is caused by the C=O stretching vibration of the PVP molecule. -1 A strong absorption peak appears at 1680 cm-1 in curves b and d, which is due to the presence of a large amount of PVP. -1The characteristic peaks near 1680 cm-1 are significantly weakened, indicating that most of the PVP is removed from the PAN / PVP nanofiber membrane. -1 The C=O peak at 2245 cm -1 The characteristic peak of the C≡N bond of PAN almost disappears, which may be due to the slight damage to the structure of PAN caused by ethanol solvent thermal treatment under long-term high temperature conditions.
[0074] Figure 5 (A) XRD patterns of a series of LPCs and C-900 prepared under different conditions. All examples show two obvious diffraction peaks near 2θ=23° and 2θ=43°. The diffraction peak at 2θ=23° represents the (002) crystal plane of the graphite structure, and the diffraction peak at 2θ=43° represents the (100) crystal plane of the graphite structure. In curve c, the diffraction peak of LPC-2-900 at 2θ=43° is more obvious, indicating that the prepared LPC-2-900 material has better graphite properties.
[0075] The carbonaceous structure can be further confirmed by Raman spectroscopy. Figure 5 (B) It can be seen that at 1350cm -1 and 1580cm -1 Two obvious characteristic peaks appear near the D peak, representing the disordered carbon structure and the bulk phase of crystalline graphite. The ratio of the D peak to the G peak intensity of LPC-2-700, LPC-2-800 and LPC-2-900 (I D / I G ) were 1.045, 0.941 and 0.938 respectively. This shows that the carbonization degree of LPCs is improved with the increase of carbonization temperature. D / I G The value is 1.133, which is because PVP and PAN are cross-linked during the pre-oxidation stabilization process, resulting in a lower degree of graphitization of C-900.
[0076] 3. Specific surface area analysis
[0077] In order to further understand the changes in the physical properties of the prepared examples, such as Figure 6 As shown in the figure, the N2 adsorption-desorption isotherms and pore sizes of PAN / PVP, PAN / PVP-EG-2, PAN / PVP-EG-3, PAN / PVP-EG-4 and a series of LPCs and C-900 were measured to evaluate their specific surface areas and pore size distributions. Figure 6As can be seen from (A), the PAN / PVP nanofiber membrane exhibits a type III isotherm, which is a typical non-porous or macroporous material. The data detected in the pore size distribution comes from the pores formed by the interlaced stacking of nanofibers. After the EG solvothermal induction treatment, obvious hysteresis loops appear in the PAN / PVP-EG-2, PAN / PVP-EG-3, and PAN / PVP-EG-4 nanotube membranes, indicating that the examples have a mesoporous structure.
[0078] As Figure 6 shown in (C), LPC-2-700 exhibits an H3-type isotherm without an obvious saturated adsorption plateau, which is a type of mesoporous material. This is because the carbonization temperature is low and the degree of pore shrinkage is low, thus maintaining the original mesoporous structure. As the carbonization temperature increases, LPC-2-800 and LPC-2-900 show a combination of type I and type IV isotherms, that is, the adsorption of N2 is basically completed at a low relative pressure (P / P0 < 0.2), and a hysteresis loop appears at a medium relative pressure (0.45 < P / P0 < 0.9), indicating that LPC-2-800 and LPC-2-900 are a micro-mesoporous structure. At the same time, BET tests were carried out and compared for C-900, LPC-3-900, and LPC-4-900. C-900 shows a type I isotherm, indicating that it is a microporous material. Compared with C-900, hysteresis loops appear in all LPCs, indicating that the EG solvothermal induction treatment can not only increase the specific surface area of the material but also construct the mesoporous structure of the material. Such a micro-mesoporous structure not only increases the specific surface area of the material but also has more application advantages.
[0079] The specific physical properties of the examples are shown in Table 2. It can be seen that during the EG solvothermal induction treatment, the specific surface area and pore volume of the PAN / PVP nanofiber membrane increase with the increase of the reaction time. The specific surface area of LPCs increases significantly from 140.867 m 2 ·g -1 to 878.909 m 2 ·g -1 , and the pore volume also increases from 0.130 cm 3 ·g -1 to 0.524 cm 3 ·g -1 . At the same time, we can also observe that the average pore diameter decreases from 3.695 nm (LPC-2-700) to 2.383 nm (LPC-2-900), which may be due to the destruction of the carbon skeleton of the examples caused by the increase of the carbonization temperature.
[0080] Table 2 Physical properties of different examples
[0081]
[0082] 4. MB adsorption performance
[0083] Figure 7 (A) shows the maximum adsorption capacity of LPC-2-900 at different MB concentrations. As the MB concentration increases, the probability of collision between LPC-2-900 and MB molecules increases, resulting in an increase in adsorption capacity. When the MB concentration reaches 300 mg / L, the adsorption capacity no longer increases significantly because the active sites of the adsorbent are fully occupied and in an adsorption saturation state. Figure 7 (B) is the curve of the adsorption amount of different examples changing with time. The adsorption amount of MB by different examples increased sharply within the first 1 hour, almost reaching 80% of the maximum adsorption amount. Subsequently, the adsorption amount increased slowly and reached adsorption equilibrium in about 3 hours. LPC-2-900 showed the best adsorption performance, which is due to the large specific surface area of LPC-2-900. More importantly, LPC-2-900 has a special micro-mesoporous structure. The micropores can provide more adsorption sites, and the mesopores can provide diffusion channels. The combination of the two plays an important role in the adsorption process. In order to evaluate the adsorption kinetics of LPC-2-900, pseudo-first-order and pseudo-second-order models were used to fit the experimental data respectively ( Figure 7 (C, D)), pseudo-first-order kinetics assumes that physical adsorption controls the adsorption rate, while pseudo-second-order kinetics assumes that chemical adsorption controls the adsorption rate by transferring electrons between the adsorbent and the adsorbate. It can be seen that the correlation coefficient R of the pseudo-second-order model 2 The fitting curve of the pseudo-second-order model is closer to the experimental data point than the pseudo-first-order model, indicating that the pseudo-second-order model can better describe the adsorption kinetics. Therefore, the adsorption process of MB by LPC-2-900 is mainly chemical adsorption, and the surface charge of the adsorbent plays an important role in the adsorption process. In order to further understand its adsorption mechanism, the isoelectric point of LPC-2-900 ( Figure 7 (E)). The isoelectric point of LPC-2-900 was found to be pH pzc =6.4. At this time, when the solution pH is less than 6.4, the surface of LPC-2-900 will be positively charged; when the solution pH is 6.4, the surface of LPC-2-900 will be uncharged; when the solution pH is greater than 6.4, some groups on the surface of LPC-2-900 will be deprotonated to make the surface negatively charged. Since MB is a cationic dye and the pH of the MB solution is 7, the electrostatic attraction between the adsorbent and the adsorbate further enhances its adsorption performance for MB.
[0084] Stability is one of the important indicators that affect the practical application of materials. In order to further evaluate the performance of LPC-2-900, a cyclic use experiment was conducted. MB solution with an initial concentration of 300 mg / L was used for 5 cycles of adsorption. Figure 7As can be seen in (F), LPC-2-900 still maintains stable adsorption performance after 5 cycles, indicating that LPC-2-900 has good stability.
[0085] The gas capture performance of LPCs and C-900 was studied by single-component CO2 adsorption. Figure 8 All samples showed a certain CO2 adsorption capacity. The maximum CO2 adsorption capacity of LPC-2-700, LPC-2-800, LPC-2-900 and C-900 were 1.68, 2.16, 2.83 and 2.10 mmol·g, respectively. -1 ; LPC-2-900 has the best CO2 capture performance, which is mainly due to its largest specific surface area and pore volume. Moreover, the unique loofah-like porous structure of LPCs provides abundant mass transfer channels for CO2 molecules, shortens the adsorption and diffusion distance of CO2 molecules, and is beneficial to the migration and storage of CO2 molecules.
[0086] 6. Analysis of the formation mechanism of loofah-like porous structure
[0087] In order to clarify the role of the EG solvothermal induction strategy in constructing a loofah-like porous nanotube membrane, a single-component PAN nanofiber membrane was prepared by electrospinning under the same conditions and then subjected to EG solvothermal induction treatment under the same conditions. Fig. 9 As shown in (d), the single-component PAN nanofibers have a smooth surface and a smaller diameter, while the PAN-EG nanofibers obtained after the EG solvent thermal treatment show a tangled and cross-linked fiber morphology ( Fig. 9 (e)), and Fig. 9 The morphology of PAN / PVP nanofibers in f changes from a smooth surface to Fig. 9 (g) Rough loofah-like flexible porous structure nanotubes of PAN / PVP-EG. In order to further explain the morphological changes of PAN / PVP nanofibers, the spinning precursor solutions of PAN, PVP and PAN / PVP were analyzed. Fig. 9 The illustrations in (ac) show the corresponding digital photos. There is no obvious difference to the naked eye, and both are uniform viscous liquids. Further observation under an optical microscope found that only the single-component PAN and PVP spinning precursor solutions showed uniform properties, while the two-component PAN / PVP spinning precursor solution showed obvious phase separation. This is mainly attributed to the PAN (R ij =29.4Mpa) and PVP(R ij=21.4Mpa) in DMF. The formation of the loofah-like porous structure can be attributed to the discontinuous phase composition of PAN / PVP nanofibers. During the EG solvent thermal induction process, PVP is easily dissolved, while the PAN component remains stable and retained. Therefore, during the EG solvent thermal induction process, the synergistic effect of the phase separation phenomenon, swelling, dissolution and crystallization of PAN and PVP molecular chains leads to the formation of the loofah-like porous nanotube film, and the loofah-like porous carbon structure is retained during the carbonization process.
[0088] In summary:
[0089] PAN / PVP two-component nanofiber membrane was prepared by electrospinning, and the PVP component was effectively removed by combining the solvent thermal induction strategy to obtain a PAN tubular membrane with a special loofah-like porous structure, indicating that only the EG solvent thermal induction strategy plays a key role in the construction of the loofah-like porous structure.
[0090] When the EG solvent thermal treatment time is 2 h and the calcination temperature is 900 °C, the best example LPC-2-900 prepared has the largest specific surface area (878.909 m 2 ·g -1 The maximum adsorption capacity of MB by this material at room temperature is 528.6 mg·g -1 The cycle performance is good. The maximum CO2 capture performance at 273K, 101kPa is 2.83mmol·g -1 .
[0091] The above are only preferred embodiments of the present invention and the technical principles used. Those skilled in the art will understand that the present invention is not limited to the specific embodiments described herein, and that various obvious changes, readjustments and substitutions can be made by those skilled in the art without departing from the scope of protection of the present invention. Therefore, although the present invention is described in more detail through the above embodiments, the present invention is not limited to the above embodiments, and may include more other equivalent embodiments without departing from the concept of the present invention, and the scope of the present invention is determined by the scope of the appended claims.
Claims
1. A method for preparing a loofah-like flexible porous carbon nanotube film, characterized in that: The following steps are involved: Dissolving polyacrylonitrile and polyvinyl pyrrolidone in N,N-dimethylformamide and stirring to obtain a uniform precursor spinning solution; The precursor spinning solution is subjected to electrostatic spinning and drying to obtain a PAN / PVP nanofiber membrane; The PAN / PVP nanofiber membrane is cut into preset sizes, placed in a high-pressure reactor, ethylene glycol is added, a solvent thermal induction reaction is carried out, and then it is repeatedly washed with deionized water to obtain a bionic loofah-like porous PAN nanotube membrane, and then a calcination carbonization reaction is carried out to obtain a loofah-like flexible porous carbon nanotube membrane.
2. The method for preparing the loofah-shaped flexible porous carbon nanotube film according to claim 1, characterized in that: The mass ratio of the polyacrylonitrile to the polyvinyl pyrrolidone is 1:1, and the concentration of the polyacrylonitrile in the N,N-dimethylformamide is 1 g / mL.
3. The method for preparing the loofah-shaped flexible porous carbon nanotube film according to claim 1, characterized in that: The concentration of the polyacrylonitrile relative to the ethylene glycol was 0.3 g / mL.
4. The method for preparing the loofah-shaped flexible porous carbon nanotube film according to claim 1, characterized in that: During the electrostatic spinning process, a collecting device is used to collect the electrostatic spinning product, the spinning temperature is 20-30° C., the relative humidity is 40-50%, and a 11-13 kV DC high voltage is connected.
5. The method for preparing the loofah-shaped flexible porous carbon nanotube film according to claim 1, characterized in that: During the drying process after electrospinning, the drying temperature is 50-70° C. and the drying time is 1-3 hours.
6. The method for preparing the loofah-shaped flexible porous carbon nanotube film according to claim 1, characterized in that: During the solvent thermal induction reaction, the reaction temperature is 170-190° C. and the reaction time is 2-4 hours.
7. The method for preparing the loofah-shaped flexible porous carbon nanotube film according to claim 1, characterized in that: During the calcination and carbonization reaction, the temperature is slowly increased to 260-280°C at a rate of 1-2°C / min in an air atmosphere and kept warm for 1-3 hours, and then the temperature is increased to 700-900°C at a rate of 2-4°C / min in an argon atmosphere and kept warm for 1-3 hours.
8. A loofah-like flexible porous carbon nanotube film, characterized in that: Prepared by the preparation method according to any one of claims 1 to 7.
9. An application of a loofah-shaped flexible porous carbon nanotube film, characterized in that: The loofah-shaped flexible porous carbon nanotube membrane according to claim 8 is used in the adsorption of organic pollutants.
Citation Information
Patent Citations
Method for preparing polyacrylonitrile-based porous hollow carbon fibers by coaxial electrospinning
CN102691136A
Preparation method of porous nano carbon fibers
CN108385209A
Preparation method and application of nitrogen-doped porous carbon fiber material
CN111235698A
Multi-pore-passage carbon-based electrode of sodium ion battery and preparation method of multi-pore-passage carbon-based electrode
CN112038630A
Porous multi-hollow flexible composite nanofiber membrane material and preparation method thereof
CN113073426A